2007
DOI: 10.1097/sle.0b013e31803c766a
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Metastatic Melanoma to the Gallbladder: Is Laparoscopic Cholecystectomy Indicated?

Abstract: Metastatic involvement of the gallbladder in melanoma is rare, but constitutes the most common metastatic lesion involving this organ. The surgical management seems to be indicated for patients with isolated and resectable gallbladder metastases to avoid symptoms or tumor complications. We report on a case of a young woman with an isolated metastatic gallbladder melanoma who presented with symptoms of acute cholecystitis. The patient underwent laparoscopic cholecystectomy (LC) and lymphadenectomy of the hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…Seelig et al [24] and Tuveri et al [25] both reported a 20-and 60-month survival, respectively, in patients treated with laparoscopic cholecystectomy. This finding is supported by Kohler et al [8] and by Samplaski et al [26] who supported the suitability of laparoscopic cholecystectomy in patients with metastatic melanoma of the gallbladder.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Seelig et al [24] and Tuveri et al [25] both reported a 20-and 60-month survival, respectively, in patients treated with laparoscopic cholecystectomy. This finding is supported by Kohler et al [8] and by Samplaski et al [26] who supported the suitability of laparoscopic cholecystectomy in patients with metastatic melanoma of the gallbladder.…”
Section: Discussionmentioning
confidence: 98%
“…Of course, a clinical history of cutaneous melanoma is more suggestive of secondary lesions and the immunohistochemical marker HMB45 could rule out the presence of junctional activity, which is typical of the primitive tumor. However, cutaneous melanoma could have a spontaneous regression and junctional activity could be present in advanced metastatic disease as well, or it could be missing in the primitive lesion characterized by a rapid growth which makes diagnosis challenging [8,25].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In an analysis of 687 necropsies of patients with renal cell carcinoma, four cases had MGBs [3] . However, the data available on MGBs are only from autopsy series of certain malignancies such as melanoma or renal cell carcinoma, or reviews of a certain metastatic carcinoma to the GB such as melanoma [6,7] , or in the form of single case reports of tumors such as melanoma [8][9][10][11] , breast cancer [4] , and hepatocellular carcinoma [5] . Furthermore, there is limited data on the proportion of MGBs among GB malignancies.…”
Section: Discussionmentioning
confidence: 99%